The Feldstein-Horioka fact - Domenico Giannone; Michele Lenza (European Central Bank (ECB), 2008)
This paper shows that general equilibrium effects can partly rationalize the high correlation between saving and investment rates observed in OECD countries. We find that once controlling for general equilibrium effects the saving-retention coefficient remains high in the 70's but decreases considerably since the 80's, consistently with the increased capital mobility in OECD countries.
Keywords: C23; F32; F41; 330; Capital Mobility; Dynamic Factor Model; International Comovement; Saving-Investment Correlation; Kapitalmobilität; Sparen; Investition; Kapitalmobilität; Theorie; OECD-Staaten